Profile of Arachidonic Acid-Derived Inflammatory Markers and Its Modulation by Nitro-Oleic Acid in an Inherited Model of Amyotrophic Lateral Sclerosis - Trostchansky, Andrés; Mastrogiovanni, Mauricio; Miquel, Ernesto; Rodríguez-Bottero, Sebastián; Martínez-Palma, Laura; Cassina, Patricia; Rubbo, Homero (Frontiers in Molecular Neuroscience, 2018)
The lack of current treatments for Amyotrophic Lateral Sclerosis (ALS) highlights the need of a comprehensive understanding of the biological mechanisms of the disease. A consistent neuropathological feature of ALS is the extensive inflammation around motor neurons and axonal degeneration, evidenced by accumulation of reactive astrocytes and activated microglia. Final products of inflammatory processes may be detected as a screening tool to identify treatment response. Herein, we focus on a) detection of arachidonic acid (AA) metabolization products by lipoxygenase (LOX) and prostaglandin endoperoxide H synthase (PGHS) in SOD1G93A mice and b) evaluate its response to the electrophilic nitro-oleic acid (NO2-OA) Regarding LOX-derived products, a significant increase in 12-hydroxyeicosatetraenoic acid (12-HETE) levels was detected in SOD1G93A mice both in plasma and brain whereas no changes were observed in age-matched non-Tg mice at the onset of motor symptoms (90 days-old). In addition, 15-hydroxyeicosatetraenoic acid (15-HETE) levels were greater in SOD1G93A brains compared to non-Tg. Prostaglandin levels were also increased at day 90 in plasma from SOD1G93A compared to non-Tg being similar in both types of animals at later stages of the disease. Administration of NO2-OA 16 mg/kg, subcutaneously (s/c) three times a week to SOD1G93A female mice, lowered the observed increase in brain 12-HETE levels compared to the non-nitrated fatty acid condition, and modified many others inflammatory markers. In addition, NO2-OA significantly improved grip strength and rotarod performance compared to vehicle or OA treated animals. These beneficial effects were associated with increased hemeoxygenase 1 (HO-1) expression in the spinal cord of treated mice co-localized with reactive astrocytes. Furthermore, significant levels of NO2-OA were detected in brain and spinal cord from NO2-OA -treated mice indicating that nitro-fatty acids (NFA) cross brain blood barrier (BBB) and reach the central nervous system to induce neuroprotective actions. In summary, we demonstrate that LOX-derived oxidation products correlate with disease progression. Overall, we are proposing that key inflammatory mediators of AA-derived pathways may be useful as novel footprints of ALS onset and progression as well as NO2-OA as a promising therapeutic compound.